PENGUATAN MANAJEMEN USAHA DAN STRATEGI PEMASARAN UMKM MELALUI KKN UMD UNEJ DI DESA KLAMPOKAN, PANJI, SITUBONDO - Rosyady, Muhammad Ghufron Rosyady; Khoirunnisa, Wilda; Unerly, Ashon Alrossy; Gena, Muhammad Sami Makarim; Rizkika, Aghnia Rahma; Mauriza, Risya; Mukaromah, Awalia Malikhatul; Nuraini, Alifia Siti; Wardhana, Ega; Putera, Dimas Fajar; Cahyani, Fariska Aulia Gita; Wicaksono, Satrio; Ilhami, Mochamad Akhsin (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2024)
UNEJ UMD KKN is the theme in the implementation of KKN 2023. The implementation of KKN UMD focuses on one project, where this project supports the Sustainable Development Goals (SDGs) of the Village. The selection of work programs in Klampokan Village, Panji, Situbondo is the assistance and development of MSMEs. Micro, Small and Medium Enterprises (MSMEs) are productive businesses in the form of individual business entities that can develop and be consistent in the national economy. It is important for an entrepreneur to produce decent and quality products to be sold in the public market. Strengthening business management supports an entrepreneur in the process of advancing their business products. An entrepreneur must also have the ability to expand the products produced, commonly known as marketing strategies. The existence of a creative and innovative marketing strategy is an effort to achieve goals in expanding market reach. This research was conducted in Klampokan Situbondo Village to improve the quality of competitiveness so as to expand market reach and the economy of this village can develop sustainably and have a positive impact on community welfare and local economic development.